Event-Driven Architecture: Building Responsive Enterprise Systems - Sagar Chaudhari, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and implementation of Event-Driven Architecture (EDA) in modern enterprise systems. It explores the fundamental components, patterns, and best practices that enable organizations to build responsive and scalable applications. The article analyzes various aspects of EDA implementation, including message broker selection, schema design, and performance optimization strategies, while providing detailed insights into real-world applications across different industries. Through extensive analysis of deployment scenarios and performance metrics, the article demonstrates how EDA transforms traditional request-response patterns into dynamic, asynchronous communication models that significantly enhance system responsiveness, operational efficiency, and business outcomes.
Keywords: Architecture scalability; Event-driven systems; Message broker integration; Near Real-time processing; System optimization